Auditoría de control interno y el nivel de cumplimiento del departamento de compras públicas del GAD municipal de Quevedo, año 2012 - Herrera Salvatierra, Yadira Leonor (2015)
This research study entitled "Audit of Internal Control and Compliance Level Public Procurement Department of the Municipal GAD Quevedo, 2012," having as variables specific components of internal control in accordance with the rules of the Comptroller General, purchasing policies established by the municipal administration and reasonable assurance of internal control, this research was based with the theoretical framework through various authors criteria that validate the study process. Analytical methods such as inductive and deductive, the type of research used was field, literature, having as sources were used; primary from officers and employees of the department, school is based on obtaining information that was taken from the Internet, books on the subject of research, the techniques used are observation, questionnaires and interviews. The research results show the evaluation of internal control by COSO I where 25 questions which reflected the following weaknesses were applied: deficiency in the payment process does not own through a process of training human talent, lacks a physical space to file extensive documentation properly and the lack of good communication between boss and coworkers that allows the fulfillment of its activities quickly and timely. The level of compliance with the Internal Control department that has public purchases is 83% which is "high", while a risk level of 17% was found to be the "low" GAD policies Municipal Quevedo are given to human talent working in different areas and through the evaluation that took place in the procurement department determined that the degree of confidence of the operating system is reliable.